A garden to keep eaudiobook - Turner, Jamie Langston (Derby, 2003)
Author of Some Wildflower in My Heart (K1001), Jamie Langston Turner won the Christy Award with A Garden to Keep. Elizabeth Landis is learning that God works in mysterious ways, and life has become more fulfilling for her as she takes Him into her heart. When she discovers her husband has been unfaithful, the Lord's strength becomes more valuable than ever.